A Bibliometric Analysis of Digital Literacy and Social Enterprise Development - Judijanto, Loso (Westscience Press, 2025)
This study presents a comprehensive bibliometric analysis of scholarly research at the intersection of digital literacy and social enterprise development. Drawing data from the Scopus database (2000–2024) and using VOSviewer for visualization, the study examines publication trends, thematic clusters, author co-citations, and country collaborations. The analysis reveals that digital literacy is a central and foundational theme, closely linked with digital transformation, e-learning, financial literacy, and digital skills. Emerging keywords such as artificial intelligence and social media indicate a shifting focus toward advanced technologies and digital engagement strategies in the social innovation domain. Southeast Asian countries, particularly Indonesia and Malaysia, are shown to be leading contributors, while broader international collaboration remains limited. Prominent scholars such as Hair J.F., Davis F.D., and Brynjolfsson E. are identified as key influencers. The findings highlight the need for future research to enhance theoretical integration, address impact measurement, and foster global academic partnerships. This study provides valuable insights for academics, practitioners, and policymakers seeking to strengthen digital capacity and innovation in the social enterprise sector.